Recent Updates On Medicinal Potentiality of Fabaceae Family: Critical Review - Priyanka Jadhavar; Dr. Seema Deshpande (International Journal of Pharma and Bio Sciences, 2022)
Use of Wild plants for medicinal purposes is an ancient tradition that has endured in many rural communities in India. In recent times, the practice of herbal medicine is decreasing. Thus in the rejuvenation of traditional herbal medicines, it is an effort to record the valuable ethno-botanical and ethno-medicinal knowledge. This review covers all aspects of medicinal importance of the Fabaceae family that were missed by some reviewers. Most of the review studies focused on the antibacterial activity of the Fabaceae family but rarely covered all other aspects as well as general health benefits of family Fabaceae in the day to day life. Some important and new aspects such as anticancer, anti-inflammatory, antiviral, antioxidant are also covered in this review article. Several research data have been published in the last decades on this concept but it is noticed that there is no single overview which can cover all medicinal properties of family Fabaceae in a single draft. Under these circumstances present review will serve as a pathfinder to researchers who have keen interest in medicinal properties of Fabaceae. Aim of our study is to focus on all medicinal activities of family Fabaceae and the main objective of this study is to collect new research and review articles using data from Medline, Pubmed, Scopus, Embase etc. The secondary metabolites of this family are very different, including the class of flavonoids, phenolic acids, tannins, anthocyanins, coumarins, saponins, Phyto-steroids and terpenoids. Due to the presence of all these secondary metabolites, it is the second-largest family to be used with therapeutic resources all over the world. Studies reveal important bioactive properties related to different genera and species, such as: analgesic activity, anti-inflammatory, anticancer, antidiabetic, antirheumatic, antimicrobial, antibacterial, cytotoxic, Antioxidant, antiproliferative, anti-leishmania, healing, cardioprotective, myorelaxant, antiulcerogenic, serine protease inhibition, chemoprotective and anti-wrinkles.